FILM ANIMASI 2 DIMENSI, “JACK THE CHICKEN!” - Ari Bakkas Pratama; Mahendradewa Suminto; Andri Nur Patrio (Institut Seni Indonesia Yogyakarta, 2019)
Animated movie “Jack The Chicken” tells story about a chicken named Jack that bored and ungrateful with anything that are given by his master. This animation tells the audiences about being grateful for everything they’ve got. This animation video has three minutes duration with simple character design. This animated movie setting and scenes are largely supported by its background and backsound because it has no dialogues. This movie was made with 2D technique where most of the creation processes were done digitally. These digital processes were done to make the works easier and shorten the duration of the works. Manual work progress also had been done especially on early stages of creation e.g. idea developing and character design.